RELATIONSHIPS BETWEEN TOBACCO MOSAIC VIRUS AND THE NON-VIRUS PROTEINS - Commoner, Barry (The Rockefeller University Press, 1955)
1. The non-virus proteins, A4, B3, and B6, characteristically found in tobacco leaf infected with TMV exhibit specific immunochemical cross-reactions with serum prepared against the virus. The close immunochemical relations which occur among these proteins do not extend to any normal tobacco leaf proteins. 2. The rate of appearance of the non-virus proteins in newly infected cultured leaf tissue at various times after inoculation has been determined by immunochemical techniques and by direct isolation of the proteins. Both methods give comparable results. The non-virus proteins appear abruptly at about 220 hours after inoculation, when the TMV content is about one-third its final value. The amount of A4 rises rapidly and then levels off. The B6 content rises rapidly and continuously over the course of the experiment. B3 appears last, and increases in amount considerably more slowly than A4 and B6. 3. The isotope contents of TMV, B3, and B6 which appear in given intervals after inoculation in newly infected leaf cultured in nutrient containing N(15)H(4) have been compared. The isotope levels of concurrent TMV, B3, and B6 are identical within the experimental error. The isotope conditions employed in this experiment lead to the conclusion that this coincidence of N(15) levels means that the virus and non-virus proteins are probably synthesized at about the same time from the same non-protein source of nitrogen. 4. Possible interpretations of the available data on the non-virus proteins are discussed. It is likely that one or more of these proteins represents small protein units which occur in the TMV nucleoprotein.As they exist in the infected leaf, the non-virus proteins are probably no longer available to the biochemical processes which lead to TMV synthesis. They are probably not precursors of TMV protein in a temporal sense.